2020
DOI: 10.1111/geb.13099
|View full text |Cite
|
Sign up to set email alerts
|

Global‐scale characterization of turning points in arid and semi‐arid ecosystem functioning

Abstract: Aim: Changes in dryland ecosystem functioning are threatening the well-being of human populations worldwide, and land degradation, exacerbated by climate change, contributes to biodiversity loss and puts pressures on sustainable livelihoods. Here, abrupt changes in ecosystem functioning [so-called turning points (TPs)] were detected using time series of Earth observation data. Hotspot areas of high TP occurrence were identified, observed changes characterized and insights gained on potential drivers for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…2. Abrupt changes or turning points in land cover (i.e., when the functioning of an ecosystem changes significantly, but not necessarily in an irreversible manner [38]) were identified over the areas in the past [9]. 3.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…2. Abrupt changes or turning points in land cover (i.e., when the functioning of an ecosystem changes significantly, but not necessarily in an irreversible manner [38]) were identified over the areas in the past [9]. 3.…”
Section: Study Areamentioning
confidence: 99%
“…The area was considered to be under the imminent threat of desertification in the future [6]. Nevertheless, many studies indicated that since this period, the Sahel experienced significant re-greening, showing the resilient character of the region [7,8] and the existence of so-called turning points in the region [9]. Besides the influence of climatology, anthropogenic activities also strongly affect land cover and vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the methods in the first category aim to control the influence of precipitation and/or temperature trends to detect permanent degradation [7,23]. The rain use efficiency (RUE) as proposed by [19]-the ratio of NPP to rainfall-has been used as an indicator of degradation [7,17,20,26,27] and ecosystem functioning [18,28]. The residual trend analysis (RESTREND) method as proposed by [11] was used frequently to estimate changes in productivity by relating annual maximum NDVI and precipitation [11,13,25,29].…”
Section: Introductionmentioning
confidence: 99%
“…In rainfall limited ecosystems, interpreting vegetation dynamics requires decoupling NDVI from rainfall variability. This can be achieved using the Rain Use Efficiency (RUE): the NPP per unit of rainfall [22][23][24][25]. The basis of this measure is that if vegetation declines in synchrony with rainfall, then the RUE will remain constant-indicating stable ecosystem condition.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, if NPP declines under constant rainfall, the RUE would decline-indicating deteriorating ecosystem condition. Trends in RUE have been used to assess broad level ecosystem condition, while shifts in RUE have been related to the linkages of human and climatic drivers on ecosystem function [20,23,25].…”
Section: Introductionmentioning
confidence: 99%